Niall W. Slater, Spectator Politics. Metatheatre and Performance in Aristophanes , Philadelphia, University of Pennsylvania Press, 2002, x + 362 pp. - Fernández, Claudia Nélida (2003)
Fil: Fernández, Claudia Nélida. Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación; Argentina.